Indonesian Government’s COVID-19 Measures, January–May 2020: Late Response and Public Health Securitization - Tangguh Chairil (Jurnal Ilmu Sosial dan Ilmu Politik, 2020)
The Indonesian government’s measures to control the coronavirus disease 2019 (COVID-19) pandemic can be characterized by late response due to initial de-securitization of the issue, and later securitization that limits its very efficacy in restricting the spread of the pandemic. This article uses securitization theory to analyze the government’s measures to control the COVID-19 pandemic and discusses how the government’s increasing reliance on military figures and national security agencies influences the measures used to control the COVID-19 pandemic. This study finds that initially, the government seemed to be trying to de-securitize the issue, denying warnings that the virus might have existed undetected in Indonesia. Then, after the first cases were confirmed in March 2020, the government responded by securitizing the issue. The delay in the government’s response to COVID-19 caused the audience to not fully accept the government’s securitization efforts because public trust in the government’s measures was already low, while the means of emergency action taken by the government against the threat of COVID-19 are also limited. The government has also been overly reliant on influential military figures and national security agencies. The government also tended to downgrade the threats, lack transparency, and even use the pandemic to crack down on anti-government smears. This article concludes that the government needs to change their approach to COVID-19 measures and prioritize the human security dimension by not downgrading the threats and upholding transparency.